FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK (GGK) YANG MENJALANI TERAPI HEMODIALISA DI RSU ROYAL PRIMA MEDAN - Yona Sarastika; Kisan Kisan; Opirisnawati Mendrofa; Juwita Verawati Siahaan (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Chronic Kidney Disease is a process where the kidney gradually become out of function in more than three months. World Health Organization (WHO) states that the growth of chronic kidney disease sufferers globally in 2013 increased up to 50% from the previous year, in 2014, chronic kidney disease sufferers in United States of America increased up to 50% and every year that are approximately 200.000 people in United States of America undergoing hemodialysis. The objective of this study is to identify factors affecting the quality of life of chronic kidney disease patients that undergo hemodialysis therapy in Royal Prima Medan Hospital in 2019. This study uses descriptive analytic study with Cross Sectional approach. The population in this study are 70 people, and 70 people as samples with total sampling technique. The result of this study shows that there is no connection between age and the quality of life of chronic kidney disease patients that undergo hemodialysis therapy (p value = 0,910 > 0,05), no connection between gender and quality of life (p value = 0,599 > 0,05), no connection between education background and quality of life (p value = 0,943 > 0,05), and there is a connection between the duration of hemodialysis with quality of life (p value = 0,001 < 0,05). The patients are expected to obey the hemodialysis therapy in order to achieve a good quality of life.